Proposal for a phylogenetic subordinal classification for poecilosclerid sponges. In: Van Soest, R.W.M., van Kempen, T.M.G., Braekman, J.C. (eds) Sponges in Time and Space. Biology, Chemistry, Paleontology. Balkema, Rotterdam, pp 123-139 - Hajdu, E.; van Soest, R.W.M.; Hooper, J.N.A. (1994)
About 300 nominal genera of poecilosclerid sponges were re-evaluated searching for monophyletic assemblages within the order ...
Proceedings of the 4th International Sponge Conference, Amsterdam 1993